PAYROLL SYSTEM ON UD. MEKAR PLASTIK - Indra Wahyudi; Haryanto, SKom, MM Haryanto, SKom, MM (Jurnal Sistem Informasi, 2000)
By looking at some of the constraints faced by the U. D. PLASTIC MEKAR aboutsalary details, salary slips and making statements that in the process from workingnotes to be a paycheck is still using manual methods, so that the greater cost and timerequired to resolve the salary calculation relatively long, especially if thesecompanies some time to develop.To overcome the above requires a computerized system that can facilitate, speed upthe process and making a good paycheck calculations and reports can also save thecost.